Pastoral Care of Migrants in the Catholic Church in the Czech Republic - Němec, Damián (Ecumeny and law, 2021)
This article deals with the pastoral care of migrants in the Czech Republic. It starts from a description of the ethnic composition of inhabitants of the Czech Republic and of permanently settled foreigners from 1918 to the present. It also acquaints the reader with the principles and individual structures of pastoral care for migrants coming from special Church documents and codes of canon law. On this basis, it presents specific structures existing in the Czech Republic and evaluates them.